Pengembangan Kreativitas Siswa dalam Pembelajaran Pendidikan Agama Islam melalui Belajar Kelompok - Mohammad Riza Zainuddin (EDUKASI : Jurnal Pendidikan Islam (e-Journal), 2014)
Creativity constitutes someone ability to bear something new, well as idea and also relative reality opus in contrast to what does preexist. Each studying activity always aims, therefore aim actually that wants at reaches from creativity result study it change who tanpak will pass through behaviour or step-up on achievement that at gets, but exists supporting Factor in proteges learned creativity, namely motivates (thruster), and its resistor factor is no ambition and studying yen on self protege. And to develop protege creativity exists one of learning form that corresponds to philosophy of approaching kontruktivis is kooperatif's learning. kooperatif's learning encourages student to get active ala interaction and positive deep agglomerate. available three studying deep strategies students with agglomerate system, amongst those; Pair-Share (Coupled strategy then shared). Both of; Jigsaw (student does two functions). Third; Split-class discussion (constituting learning strategy by divides class as two to do discussions). And learning with agglomerate system can take in protege plots, formulate, work, and finding and evaluates selftaught result in one group of this studying experience, protege will get to develop self for creative.